2014
DOI: 10.5114/kitp.2014.47336
|View full text |Cite
|
Sign up to set email alerts
|

CARDIAC SURGERY Evaluation of olfactory memory after coronary artery bypass grafting

Abstract: IntroductionThis study determined whether coronary artery bypass grafting (CABG) surgery has any effect on olfactory function, employing the Brief Smell Identification Test (B-SIT).Material and methodsAll the participants were informed preoperatively about the B-SIT test and the mode of its application. The test was performed by each patient preoperatively (d0) as well as 1 (d1) and 3 (d3) days following the surgery. C-reactive protein (CRP) levels were recorded at the same time as the smell test.ResultsThis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…As is known, CRP is one of the leading positive acute phase reactants, and it routinely is used in our clinic with this feature. In our previous study, we demonstrated that olfactory functions were deteriorated with CRP levels that were elevated due to inflammation, in patients who had undergone on-pump CABG [Erdem 2014]. In the present study, we confirmed that preoperative CRP values that reflect increased inflammation negatively affected olfactory functions both in the On-Pump and Off-Pump patient groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As is known, CRP is one of the leading positive acute phase reactants, and it routinely is used in our clinic with this feature. In our previous study, we demonstrated that olfactory functions were deteriorated with CRP levels that were elevated due to inflammation, in patients who had undergone on-pump CABG [Erdem 2014]. In the present study, we confirmed that preoperative CRP values that reflect increased inflammation negatively affected olfactory functions both in the On-Pump and Off-Pump patient groups.…”
Section: Discussionsupporting
confidence: 86%
“…Also, some studies have reported that taste and smell disorders commonly are seen in patients with cardiovascular disease [Liu 2016;Seubert 2017]. Hence, in our previous study, we demonstrated that olfactory functions tended to deteriorate in the early postoperative period in patients undergoing on-pump CABG with CPB [Erdem 2014].…”
Section: Introductionmentioning
confidence: 54%
“…Postoperative changes to olfactory function are often observed following sinonasal 7 12 and neurosurgery 13 17 , especially when changes occur in areas related to olfaction such as the olfactory bulb, cribriform plate, olfactory mucosa, or nasal septum. In the last 30 years, however, postoperative changes to olfaction have been also reported in other types of surgery, such as: cardiovascular 18 , 19 , abdominal 20 23 , and genito-urinary 24 26 .…”
Section: Introductionmentioning
confidence: 99%